Frontispiece: Relaxation Dynamics and Magnetic Anisotropy in a Low‐Symmetry DyIII Complex. Issue 16 (11th April 2016) - Lucaccini, Eva; Briganti, Matteo; Perfetti, Mauro; Vendier, Laure; Costes, Jean‐Pierre; Totti, Federico; Sessoli, Roberta; Sorace, Lorenzo
Abstract : Single‐Molecule Magnets A detailed analysis of the magnetic and electronic structure of a Dy(LH)3 complex, a new single‐molecule magnet (SMM), is described by E. Lucaccini, M. Briganti, et al. in their Full Paper onpage 5552 ff., by taking advantage of single‐crystal studies, ab initio calculations, and AC magnetic measurements. These experimental and theoretical methods support each other in describing the magnetic anisotropy of the complex and give hints about the magnetic relaxation mechanisms. The picture highlights the importance of combining different techniques to get a detailed understanding of the magnetisation dynamics in lanthanide‐based SMMs.